ANALISIS STRATEGIS MANAJEMEN SUMBER DAYA MANUSIA DI PESANTREN HIDAYATUL MUBTADI-IEN KENDAL (PONDOK PESANTREN) - Hani, Umi; Astuti, Fitria Yuni (Universitas Putera Batam, 2024)
Strategic human resource management integrates the role of management with human resource through strategic roles with SWOT analysis to achieve the goals expected by an organization or institution. This research uses a qualitative descriptive type of research with the research object at the Hidayatul Mubtadi-Ien Islamic Boarding School, after carrying out a strategic analysis using SWOT analysis, can maintail the Islamic Boarding School with classical yellow book studies and Al-Qur’an tahfidz as well as weekly recitations which are in great demand by local congregations. It has a strategic location but the development of the students has decreased, and have to compete with Islamic Boarding Schools or other educational institutions, which creates a challenge for the Hidayatul Mubtadi-Ien Islamic Boarding School in the future.